Assessment of Traffic Operational Performance: A Case Study of Maharajgunj Intersection of Kathmandu Valley - Kafle, Shesh Raj; Amgain, Arbin; Kalathoki, Aarju; Bohara, Dhiraj (Journal of Engineering Issues and Solutions, 2025)
Urban intersections are important for controlling traffic and ensuring effective mobility, especially in cities that are growing speedily. Intersections are one of the major reasons of congestion in the Kathmandu valley and congestion is proving itself as the chronic disease for the road transportation. This study evaluates the operational performance of the Maharajgunj intersection which is one of the major and busy intersection at Kathmandu Valley. Using a mix of field data and numerical simulation tools, the study examines several performance parameters such as Level of Service (LoS), queue length and degree of saturation. Comprehensive data including volume count, cruise speed, back of queue (BOQ) and intersection geometry data are obtained, and incorporated into SIDRA INTERSECTION 8.0 for calibration, validation and scenario analysis. Various alternatives were explored and evaluated to improve the operational performance of the intersection.For Maharajgunj intersection,two alternatives were proposed:(1) Constructing a flyover between Basundhara and Chabahil approaches and (2) Restriction of right turn in minor approaches. In the existing condition, the intersection was performing at Level of Services (LoS) F, also average vehicles delay at 216 sec and average back of queue (BoQ) with 385.3 m. After implementing flyover, the performance improved to LoS C with a delay of 22.6 seconds and a average back of queue 121.9m , and the restriction of right turn in minor approaches yielded LoS F with a average control delay 105.6 seconds and average back of queue 333.9m. Based on comparison of performance indicators alternatives 1 shows the best results for the improvement of this intersection. It is recommended to constructed flyover on the major approaches for efficient flow of vehicles in that intersection.